LEGAL CONSEQUENCES OF DUALISM REGULATIONS ON MICRO WAQF BANK AS A SHARIA MICROFINANCE INSTITUTIONS IN INDONESIA - Prananingtyas, Paramita; Disemadi, Hari Sutra (Fakultas Hukum Universitas Muhammadiyah Magelang, 2020)
The presence of types of financial institutions in Indonesia makes it easy for people to choose which financial services they need. Micro Waqf Bank is one of the Microfinance Institutions that applies sharia principles that are currently growing and developing. However, there are legal issues related to arrangements for organizing a Micro Waqf Bank with a cooperative legal entity, namely, there are two overlapping regulations, namely the Microfinance Institution legislation, and Cooperative regulations. The purpose of this study is necessary to find out whether the legal consequences arising in the process of establishment, implementation, or if there are problems encountered by Mikro Waqf Banks as a Sharia Microfinance Institution incorporated as a cooperative. This study uses a normative legal research method with a statutory approach and conceptual approach. This study shows that the dualism of Micro Waqf Bank arrangements gives rise to contradictions in the arrangements for the establishment, guidance, and supervision. The existence of this dualism of regulation also gives rise to legal consequences in the establishment of a Micro Waqf Bank incorporated as a cooperative. The legal consequences are related to the broader aspects of business activities based on MFI regulations compared to cooperative regulations. Legal consequences related to capital aspects that require Micro Waqf Banks have a certain amount of capital by MFI regulations. Then from the aspect of coaching and supervision in which there are an examination and evaluation, there is also a dualism which in the regulation of the function of the cooperative is carried out by the Ministry of Cooperatives but the existence of the MFI regulation of the fostering and supervision function is under the authority of the Financial Services Authority.